The relationship between employer branding and talent management in manufacturing firm the mediating role of transformational leadership - Selva Raja, Hemananthiny (2023)
Operating a business in a competitive environment has pushed companies to seek out the most effective strategies for improving their talented workforce. Many prior literatures have indicated that one of the most important parts that an organization’s strategic plan should include is managing the best talent on the market. The challenge faced is to reduce the battle of red zone in talent management. At a time when companies are competing for talent, a company’s employer branding can be incredibly influential in a candidate’s consideration of working there. Therefore, it is important that organizations to implement strategies that can create leaders who can demonstrate the behaviors and be an example to their followers. This is important in building and retaining a strong talent pipeline. Thus, this study aims to investigate the relationship between employer branding and talent management and the mediating role of transformational leadership. A total of 113 middle level management employees were involved as respondents using purposive sampling. This research makes the questionnaire instrument the main research tool to collect information about the constructs involved. The findings of the study showed a positive relationship between economic, social, development, application, interest value’s, work-life balance on talent management. In addition, the findings also show that role of transformational leadership is a mediator on the relationship between employer branding and talent management. It is believed that this research paper will benefit industry practitioners and academics for future reference.